Battery reference book - Crompton, T. R. (Thomas Roy) (Oxford, England ; Boston : Newnes, 2000)
Crompton's Battery Reference Book has become the standard reference source for a wide range of professionals and students involved in designing, manufacturing, and specifying products and systems that use batteries. This book is unique in providing extensive data on specific battery types, manufacturers and suppliers, as well as covering the theory - an aspect of the book which makes an updated edition important for every professional's library. The coverage of different types of battery is fully comprehensive, ranging from minute button cells to large installations weighing several hundred tonnes. Must-have information and data on all classes of battery in an accessible form. Essential reference for design engineers in automotive and aerospace applications, telecommunications equipment, household appliances, etc. Informs you of developments over the past five years.
Introduction to battery technology -- Guidelines to battery selection -- Battery characteristics. Lead-acid secondary batteries -- Nickel batteries -- Silver batteries -- Alkaline manganese batteries -- Carbon-zinc and carbon-zinc chloride primary batteries -- Mercury batteries -- Lithium batteries -- Manganese dioxide-magnesium perchlorate primary batteries -- Magnesium-organic electrolyte primary batteries -- Metal-air cells -- High-temperature thermally activated primary reserve batteries -- Zinc-halogen secondary batteries -- Sodium-sulphur secondary batteries -- Other fast-ion conducting solid systems -- Water-activated primary batteries -- Battery theory and design. Lead-acid secondary batteries -- Nickel batteries -- Silver batteries -- Alkaline manganese batteries -- Carbon-zinc and carbon-zinc chloride batteries -- Mercury-zinc batteries -- Lithium batteries -- Manganese dioxide- magnesium perchlorate primary batteries -- Metal-air batteries -- High-temperature thermally activated primary batteries -- Zinc-halogen secondary batteries -- Sodium-sulphur secondary batteries -- Battery performance evaluation. Primary batteries -- Secondary batteries -- Battery applications. Lead-acid secondary batteries -- Nickel batteries -- Silver batteries -- Alkaline manganese primary batteries -- Carbon-zinc primary batteries -- Mercury batteries -- Lithium primary batteries -- Manganese dioxide-magnesium perchlorate primary batteries -- Metal-air batteries -- High-temperature thermally activated primary batteries -- Seawater-activated primary batteries -- Electric vehicle secondary batteries -- Battery charging. Constant-potential charging -- Voltage-limited taper current charging of alkaline manganese dioxide batteries -- Constant-current charging -- Taper charging of lead-acid motive power batteries -- Methods of charging large nickel-cadmium batteries -- Lead-acid (secondary) batteries -- Nickel batteries -- Silver batteries -- Alkaline manganese dioxide batteries -- Carbon-zinc batteries (primary) and carbon-zinc chloride batteries -- Mercury batteries -- Lithium batteries -- Manganese dioxide-magnesium perchlorate (primary) batteries -- Magnesium-organic electrolyte batteries -- Metal-air cells -- Thermally activated batteries -- Zinc-halogen batteries -- Sodium-sulphur batteries -- Water-activated batteries.
Includes bibliographical references and index.
Keywords: Electric batteries; Storage batteries; Electronic books